CPT1 deficiency blocks autophagic flux to promote lipid accumulation induced by co-exposure to polystyrene microplastic and cadmium - Chen, Zhixuan; Qu, Huayi; Sun, Jian; Wang, Tao; Yuan, Yan; Gu, Jianhong; Bian, Jianchun; Liu, Zongping; Zou, Hui (Frontiers in Pharmacology, 2025)
IntroductionCadmium (Cd) and polystyrene microplastics (PS-MPs), two ubiquitous environmental contaminants, produce unique synergistic toxicity when co-existing. Key unanswered questions include specific effects on liver function and potential mechanisms.MethodsIn this study, C57BL/6 mice and AML12 cells were used to establish in vivo and in vitro models to elucidate the effects of combined exposure to PS-MPs and Cd on the liver and their mechanisms.ResultsThe results showed that the combined effects of PS-MPs and Cd caused significantly more liver damage than exposure alone. As observed by transmission electron microscopy (TEM), the number of autophagosomes was significantly increased in the PS-MPs and Cd co-treated group. In addition, autophagic flux was assayed by RFP-GFP-LC3, a reporter system expressing dual fluorescent proteins, which showed an overwhelming enhancement of autophagic flux damage by co-exposure to PS-MPs and Cd compared to exposure alone. To further investigate the involvement of carnitine palmitoyltransferase1(CPT1) in liver injury induced by co-exposure to Cd and PS-MPs, we co-exposed Baicalin, an activator of CPT1, with PS-MPs and Cd, and showed that activation of CPT1 alleviated the impairment of autophagic fluxes induced by co-exposure of Cd and PS-MPs and further alleviated the changes in lipid accumulation and associated protein levels.DiscussionIn conclusion, the concurrent exposure of PS-MPs and Cd resulted in the blockage of hepatic lipid accumulation and autophagic pathway and further aggravated the toxic damage to the liver. Activation of CPT1 could alleviate the PS-MPs and Cd-induced lipid accumulation and autophagy pathway blockage thus reducing liver injury.